Modified carbon nanofiber and its preparation method, use and polylactic acid composition

By coating rare earth hydroxide whiskers on the surface of carbon nanofibers, modifying carbon nanofibers is solved, and the problem of insufficient binding force of existing rare earth modified carbon fibers is achieved, and significant strength and toughness improvement of polylactic acid is achieved.

CN115976823BActive Publication Date: 2025-03-28BAOTOU RESEARCH INSTITUTE OF RARE EARTHS +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310105533.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-03-28
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

Among the existing rare earth modified carbon fibers, the bonding force between rare earth compounds and carbon fibers is weak, resulting in poor reinforcement and toughening effects.

Method used

Modified carbon nanofibers were prepared by dropwise addition of rare earth soluble salt solution to the carbon nanofiber dispersion, adjusting the pH value, and hydrothermal reaction was carried out in a closed container to form rare earth hydroxide whiskers coated on the surface of the carbon nanofibers.

Benefits of technology

Modified carbon nanofibers can be evenly dispersed in polylactic acid, significantly improving the strength and toughness of polylactic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115976823B_ABST
    Figure CN115976823B_ABST
Patent Text Reader

Abstract

The invention discloses a modified carbon nanofiber and a preparation method, use and polylactic acid composition thereof. The modified carbon nanofiber of the invention is a carbon nanofiber with a rare earth hydroxide coated on the surface. The modified carbon nanofiber can improve the strength and toughness of polylactic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified carbon nanofiber, a preparation method and application thereof, and a polylactic acid composition. Background Art

[0002] Carbon nanofibers have a nanometer-scale diameter, generally between 50 and 200 nm. Carbon nanofibers have the advantages of few defects, large specific surface area, low density, high specific modulus, and high specific strength. The crack bridging and pull-out effect of rare earth hydroxide whiskers themselves have the effect of strengthening and toughening polymer materials.

[0003] CN1597774A discloses a method for preparing rare earth modified carbon fiber. The carbon fiber is placed in a muffle furnace at 450-600°C for ablation for 0.5-1h to remove organic residues on its surface. The carbon fiber is immersed in a rare earth modifier at room temperature, filtered and dried. The rare earth modifier is composed of a rare earth compound, ethanol, ethylenediaminetetraacetic acid, ammonium chloride, nitric acid and urea. The rare earth compound is lanthanum chloride, cerium chloride, lanthanum oxide or cerium oxide. In the rare earth modified carbon fiber obtained by this method, the bonding force between the rare earth compound and the carbon fiber is weak.

[0004] CN102351556A discloses a method for preparing a rare earth toughened carbon / carbon composite material. Rare earth material and ethanol are mixed into a mixed solution, and the treated carbon fiber preform is immersed in the mixed solution, ultrasonically vibrated, and the impregnated carbon fiber preform is taken out and dried. The dried impregnated carbon fiber preform is placed in a deposition chamber of a thin film boiling chemical vapor infiltration furnace for carbon deposition to obtain a rare earth toughened carbon / carbon composite material. The rare earth material is either lanthanum chloride or cerium chloride. The rare earth toughened carbon / carbon composite material obtained by the method is a membrane structure.

[0005] CN113846482A discloses a method for preparing a carbon fiber / rare earth oxide nanowire mixed reinforcement. A rare earth salt is prepared into an aqueous solution, a surfactant is added dropwise, and a sodium hydroxide solution is added dropwise to adjust the pH value to 10-13 to obtain a reaction solution. The reaction solution and the treated carbon fiber preform are placed in a reactor, and rare earth oxide nanowires are synthesized in situ after ultrasonic vibration to obtain a treated carbon fiber preform. The obtained carbon fiber preform is soaked and washed with deionized water to obtain a crude carbon fiber / rare earth oxide nanowire mixed reinforcement. The crude mixed reinforcement is calcined under nitrogen protection to obtain a finished mixed reinforcement. The carbon fiber preform is any one of carbon fiber cloth, carbon fiber integral felt, carbon fiber needle punching, and woven preform. The carbon fiber / rare earth oxide nanowire mixed reinforcement uses the carbon fiber preform as the matrix, and the rare earth oxide fails to cover the surface of the carbon fiber, so the reinforcement and toughening still need to be improved. Summary of the invention

[0006] In view of this, one object of the present invention is to provide a modified carbon nanofiber, and the rare earth hydroxide can coat the surface of the carbon nanofiber. Another object of the present invention is to provide a method for preparing the modified carbon nanofiber. Another object of the present invention is to provide the use of the modified carbon nanofiber. Another object of the present invention is to provide a polylactic acid composition. The polylactic acid composition has high strength and toughness. The above objects are achieved by the following technical solutions.

[0007] In one aspect, the present invention provides a modified carbon nanofiber, which is a carbon nanofiber with a rare earth hydroxide coated on its surface.

[0008] According to the modified carbon nanofiber of the present invention, preferably, the rare earth hydroxide exists on the surface of the carbon nanofiber in the form of whiskers.

[0009] On the other hand, the present invention provides a method for preparing the modified carbon nanofiber, comprising the following steps:

[0010] (1) adding a rare earth soluble salt solution dropwise to a carbon nanofiber dispersion to obtain a mixed solution;

[0011] (2) under stirring, adding a basic compound containing two or more amino groups dropwise to the mixed solution to adjust the pH of the mixed solution to 7 to 12; and then continuing to stir to obtain a mixture;

[0012] (3) placing the mixture in a sealed container, reacting at 210-350° C. for 30-60 hours to obtain a solid product; grinding the solid product to obtain modified carbon nanofibers.

[0013] According to the preparation method of the present invention, preferably, the dispersion medium of the carbon nano dispersion is a mixture of water and C1-C6 fatty alcohol, and the solvent of the rare earth soluble salt solution is a mixture of water and C1-C6 fatty alcohol.

[0014] According to the preparation method of the present invention, preferably, the rare earth soluble salt is selected from one or more of praseodymium chloride, praseodymium nitrate and praseodymium sulfate, and the concentration of the rare earth soluble salt solution is 0.02-0.08 mol / L.

[0015] According to the preparation method of the present invention, preferably, the basic compound containing two or more amino groups has a structure shown in formula (1):

[0016]

[0017] Here, n is an integer from 1 to 5.

[0018] According to the preparation method of the present invention, preferably, the closed container is a hydrothermal reactor with a polytetrafluoroethylene lining.

[0019] In another aspect, the present invention provides use of the modified carbon nanofibers in improving the strength and / or toughness of polylactic acid.

[0020] In another aspect, the present invention provides a polylactic acid composition comprising 15 to 35 parts by weight of polylactic acid and 0.01 to 0.5 parts by weight of the above-mentioned modified carbon nanofiber.

[0021] The polylactic acid composition according to the present invention further comprises 2 to 9 parts by weight of aromatic polyester, 0.05 to 1.5 parts by weight of antioxidant, 0.3 to 2 parts by weight of plasticizer and 0.05 to 1.5 parts by weight of vegetable oil.

[0022] The invention coats the surface of carbon nanofiber with rare earth hydroxide to form modified carbon nanofiber, which can be evenly dispersed in polylactic acid and has a good effect of improving the strength and toughness of the polylactic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a transmission electron microscope (TEM) image of the modified carbon nanofibers obtained in Example 1.

[0024] Figure 2 This is the EDS graph of the carbon element in the modified carbon nanofibers obtained in Example 1.

[0025] Figure 3 This is the EDS graph of oxygen element in the modified carbon nanofibers obtained in Example 1.

[0026] Figure 4 This is the EDS graph of the praseodymium element in the modified carbon nanofibers obtained in Example 1. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0028] <Modified carbon nanofibers and their uses>

[0029] The modified carbon nanofiber of the present invention is a carbon nanofiber with a rare earth hydroxide coated on the surface. The so-called coating means that the rare earth hydroxide covers the surface of the carbon nanofiber. The rare earth hydroxide coverage area accounts for more than 5% of the entire surface area of ​​the carbon nanofiber, preferably more than 15%, more preferably more than 50%, and most preferably more than 90%. The rare earth hydroxide coverage area accounts for less than 100% of the entire surface area of ​​the carbon nanofiber, such as less than 85%, and for example less than 50%. 100% means complete coverage.

[0030] Rare earth hydroxide is present in the form of whiskers on the surface of carbon nanofibers. Such modified carbon nanofibers can be evenly dispersed in polylactic acid, and the strength and toughness of polylactic acid can be better improved. In certain embodiments, the rare earth hydroxide is preferably praseodymium hydroxide. The present invention finds that such modified carbon nanofibers can be better dispersed in polylactic acid, and the strength and toughness of polylactic acid can be better improved.

[0031] The modified carbon nanofibers of the present invention can be uniformly dispersed in polylactic acid to improve the strength and toughness of polylactic acid. Therefore, the present invention provides the use of the modified carbon nanofibers in improving the strength and / or toughness of polylactic acid. Specifically, the strength is tensile strength. Toughness is elongation at break.

[0032] <Method for preparing modified carbon nanofiber>

[0033] The method for preparing the modified carbon nanofiber of the present invention comprises the following steps: (1) a mixed solution preparation step; (2) a mixture preparation step; and (3) a reaction and grinding step. The method of the present invention can coat the surface of the carbon nanofiber with rare earth hydroxide whiskers without using additives such as surfactants and dispersants.

[0034] Mixture preparation steps

[0035] The rare earth soluble salt solution is added dropwise to the carbon nanofiber dispersion to obtain a mixed solution.

[0036] The rare earth soluble salt can be selected from one or more of rare earth chlorides, rare earth nitrates, and rare earth sulfates. Preferably, the rare earth soluble salt is selected from one or more of praseodymium chloride, praseodymium nitrate, or praseodymium sulfate. More preferably, the rare earth soluble salt is praseodymium chloride. The rare earth soluble salt can be used in the form of its hydrate.

[0037] The solvent of the rare earth soluble salt solution is a mixture of water and C1-C6 fatty alcohol. C1-C6 fatty alcohol is a monohydric alcohol containing 1-6 carbon atoms; preferably a monohydric alcohol containing 1-3 carbon atoms. Examples of alcohols include, but are not limited to, methanol, ethanol, propanol, and isopropanol. Most preferably, the alcohol is ethanol. The mass ratio of alcohol to water can be 3:(5-15); preferably 3:(6-10); more preferably 3:(7-8). This can better dissolve the rare earth soluble salt, which is conducive to the formation of rare earth hydroxide whiskers on the surface of carbon nanofibers.

[0038] The concentration of the rare earth soluble salt solution can be 0.02-0.08 mol / L, preferably 0.03-0.06 mol / L, and more preferably 0.04-0.05 mol / L, which is conducive to dispersing the rare earth soluble salt on the surface of the carbon nanofibers.

[0039] The solvent of the carbon nanofiber dispersion is a mixture of water and C1-C6 fatty alcohol. C1-C6 fatty alcohol is a monohydric alcohol containing 1-6 carbon atoms; preferably a monohydric alcohol containing 1-3 carbon atoms. Examples of alcohols include, but are not limited to, methanol, ethanol, propanol, and isopropanol. Most preferably, the alcohol is ethanol. The mass ratio of alcohol to water can be (2-7):3; preferably (3-6):3; more preferably (4-5):3. This can improve the uniformity of the dispersion.

[0040] The content of the carbon nanofibers in the carbon nanofiber dispersion may be (0.01-0.1) g / L, preferably (0.02-0.08) g / L, and more preferably (0.02-0.04) g / L.

[0041] The mass ratio of the rare earth soluble salt to the carbon nanofiber in the mixed solution can be (20-40): 1, preferably (25-35): 1, and more preferably (30-35): 1. The modified carbon nanofibers formed in this way can better improve the strength and toughness of polylactic acid.

[0042] Mixture preparation steps

[0043] Under stirring conditions, a basic compound containing two or more amino groups is added dropwise to the mixed solution to adjust the pH of the mixed solution to 7-12; and then stirring is continued to obtain a mixture.

[0044] The stirring may be magnetic stirring or mechanical stirring. According to one embodiment of the present invention, the stirring is magnetic stirring.

[0045] The chemical structure of a basic compound containing two or more amino groups is shown in formula (1):

[0046]

[0047] Wherein, n is an integer of 1 to 5. Preferably, n is an integer of 1 to 3.

[0048] Examples of alkaline compounds containing two or more amino groups include, but are not limited to, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine. Preferably, the alkaline compound containing two or more amino groups is diethylenetriamine. This helps to form rare earth hydroxide whiskers, improve the purity of the modified carbon nanofibers, and enhance the toughening effect on polylactic acid.

[0049] In the present invention, the pH of the mixed solution is adjusted to 7 to 12, preferably to 8 to 11, and more preferably to 8 to 9. This is conducive to the formation of rare earth hydroxide whiskers.

[0050] The stirring time may be 2 to 8 hours, preferably 3 to 6 hours, and more preferably 4 to 5 hours.

[0051] Reaction and grinding steps

[0052] The mixture is placed in a sealed container and reacted at 210-350° C. for 30-60 hours to obtain a solid product; the solid product is ground to obtain modified carbon nanofibers.

[0053] The sealed container can be a hydrothermal reactor with a polytetrafluoroethylene liner, which helps to improve the purity of the modified carbon nanofibers.

[0054] The reaction temperature is 210 to 350°C, preferably 250 to 300°C, and more preferably 270 to 290°C.

[0055] The reaction time is 30 to 60 hours, preferably 35 to 50 hours, and more preferably 40 to 45 hours.

[0056] The product obtained by the reaction can be cooled and then filtered to obtain a solid product.

[0057] The solid product may be washed and dried before grinding.

[0058] The solid product can be washed alternately with water and ethanol. The number of washings can be multiple times, such as 6 times, 8 times, etc.

[0059] The drying pressure may be 0.01 to 0.1 MPa, preferably 0.05 to 0.1 MPa, and more preferably 0.05 to 0.08 MPa.

[0060] The drying temperature may be 40 to 90°C, preferably 50 to 80°C, and more preferably 60 to 70°C.

[0061] The drying time may be 12 to 48 hours, preferably 15 to 40 hours, and more preferably 20 to 30 hours.

[0062] <Polylactic acid composition>

[0063] The polylactic acid composition of the present invention comprises polylactic acid and the above-mentioned modified carbon nanofiber. In certain embodiments, the polylactic acid composition of the present invention comprises polylactic acid, aromatic polyester, antioxidant, plasticizer, vegetable oil and the above-mentioned modified carbon nanofiber. In certain embodiments, the polylactic acid composition is composed of polylactic acid, aromatic polyester, antioxidant, plasticizer, vegetable oil and modified carbon nanofiber.

[0064] The amount of polylactic acid used is 15 to 35 parts by weight, preferably 18 to 30 parts by weight, and more preferably 20 to 25 parts by weight.

[0065] The aromatic polyester can be selected from one or more of polybutylene terephthalate, polyethylene terephthalate, U-polymer and polydiallyl terephthalate. Preferably, the aromatic polyester is selected from one or more of polybutylene terephthalate and polyethylene terephthalate. According to one embodiment of the present invention, the aromatic polyester is polybutylene terephthalate. This can improve the strength and toughness of the polylactic acid composition.

[0066] The amount of the aromatic polyester is 2 to 9 parts by weight, preferably 4 to 8 parts by weight, and more preferably 6 to 7 parts by weight, which can improve the strength and toughness of the polylactic acid composition.

[0067] The antioxidant may be selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant DNP, antioxidant DLTP and antioxidant TPP. Preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076 and antioxidant CA. More preferably, the antioxidant is antioxidant CA.

[0068] The amount of antioxidant used is 0.05 to 1.5 parts by weight; 0.1 to 1 part by weight; more preferably 0.3 to 0.7 part by weight.

[0069] The plasticizer may be an ester plasticizer. The ester plasticizer may be a methacrylate plasticizer or a citrate plasticizer. According to one embodiment of the present invention, the plasticizer is methacrylate glycerol. Such a plasticizer can be more evenly dispersed in the polylactic acid composition.

[0070] The amount of plasticizer used can be 0.3 to 2 parts by weight, preferably 0.5 to 1 part by weight, and more preferably 0.6 to 0.8 part by weight.

[0071] The vegetable oil can be selected from one or more of soybean oil, corn oil, peanut oil, sunflower seed oil, linseed oil, castor oil and rapeseed oil. Preferably, the vegetable oil is selected from one or more of soybean oil, corn oil and peanut oil. More preferably, the vegetable oil is soybean oil.

[0072] The amount of vegetable oil used is 0.05 to 1.5 parts by weight, preferably 0.1 to 1 part by weight, and more preferably 0.4 to 0.8 part by weight.

[0073] The amount of modified carbon nanofiber is 0.01 to 0.5 parts by weight, preferably 0.05 to 0.3 parts by weight, and more preferably 0.8 to 0.12 parts by weight, which can better improve the strength and toughness of polylactic acid.

[0074] The elongation at break of the polylactic acid composition is greater than or equal to 150%, preferably greater than or equal to 170%, and more preferably greater than or equal to 210%. The elongation at break of the polylactic acid composition may be less than or equal to 300%, and may also be less than or equal to 250%.

[0075] The tensile strength of the polylactic acid composition is greater than or equal to 30 MPa, preferably greater than or equal to 35 MPa, and more preferably greater than or equal to 37 MPa. The tensile strength of the polylactic acid composition may be less than or equal to 50 MPa, and may also be less than or equal to 40 MPa.

[0076] The polylactic acid composition can be prepared by the following steps: polylactic acid, aromatic polyester, antioxidant, plasticizer, vegetable oil and modified carbon nanofiber are mixed, and then injection molded in a twin-screw extruder to obtain the polylactic acid composition.

[0077] The distance between the two rollers in the twin-screw extruder may be 0.2 to 0.8 mm, preferably 0.3 to 0.6 mm, and more preferably 0.4 to 0.5 mm.

[0078] The temperature difference between the two rollers can be 10-40°C, preferably 20-35°C, and more preferably 25-30°C. The temperatures of the two rollers can be 100-170°C and 170-200°C, respectively; preferably, the temperatures of the two rollers are 130-160°C and 175-190°C, respectively; more preferably, the temperatures of the two rollers are 140-155°C and 180-185°C, respectively.

[0079] Here is the test method:

[0080] Elongation at break and tensile strength: The polylactic acid composition is pressed into a dumbbell-shaped sheet sample by an air compressor. The dumbbell-shaped sheet sample is vertically clamped on an electronic universal testing machine and subjected to a tensile test at 25°C according to the method specified in GB / T1040.1-2006 Determination of tensile properties of plastics. Three samples are taken for each material to be tested, and the average value is taken to record the sample thickness, elongation at break and tensile strength.

[0081] Example 1

[0082] The carbon nanofibers were stirred and mixed with a mixture of water and ethanol (the mass ratio of ethanol to water was 4:3) to form a carbon nanofiber dispersion (the content of the carbon nanofibers was 0.025 g / mL).

[0083] A praseodymium chloride solution with a concentration of 0.04 mol / L (the solvent is ethanol and water in a mass ratio of 3:8) is added dropwise to the carbon nanofiber dispersion to obtain a mixed solution (the mass ratio of praseodymium chloride to carbon nanofiber is 30:1).

[0084] Under magnetic stirring, diethylenetriamine was added dropwise to the mixed solution until the pH of the mixed solution reached 9, and then the addition was stopped. The magnetic stirring was continued for 4 hours to obtain a mixture.

[0085] The mixture was placed in a hydrothermal reactor with a polytetrafluoroethylene liner and reacted at 280°C for 40 hours to obtain a reaction product. The reaction product was cooled to 25°C and then filtered to obtain a solid product. The solid product was washed alternately with deionized water and ethanol, and then dried at a pressure of 0.06 MPa and a temperature of 60°C for 24 hours. The dried product was ground to obtain modified carbon nanofibers.

[0086] from Figure 1 It can be seen that praseodymium hydroxide is evenly coated on the carbon nanofibers, with a coverage rate of more than 90%. Figure 2-4 The existence of C, O, and Pr elements was proved to be praseodymium hydroxide and carbon nanofibers.

[0087] Examples 2 to 4 and Comparative Example 1

[0088] Polylactic acid, polybutylene terephthalate, antioxidant CA (1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane), methacrylate glycerol, soybean oil and the modified carbon nanofiber of Example 1 were mixed uniformly, and then injection molded in a twin-screw extruder to obtain a polylactic acid composition. The roller spacing of the twin-screw extruder was 0.40 mm.

[0089] Table 1

[0090]

[0091] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing modified carbon nanofibers for improving the strength and / or toughness of polylactic acid, characterized in that: The steps include: (1) adding a rare earth soluble salt solution dropwise to a carbon nanofiber dispersion to obtain a mixed solution; the concentration of the rare earth soluble salt solution is 0.02-0.08 mol / L, the content of carbon nanofibers in the carbon nanofiber dispersion is 0.01-0.1 g / L, and the mass ratio of the rare earth soluble salt to the carbon nanofibers in the mixed solution is (20-40):1; the rare earth soluble salt is selected from one or more of praseodymium chloride and praseodymium sulfate; (2) under stirring, adding a basic compound containing two or more amino groups dropwise to the mixed solution to adjust the pH of the mixed solution to 7 to 12; and then continuing to stir to obtain a mixture; (3) placing the mixture in a sealed container and reacting at 250-300° C. for 30-60 hours to obtain a solid product; grinding the solid product to obtain modified carbon nanofibers; The basic compound containing two or more amino groups has a structure shown in formula (1): Wherein, n is an integer from 1 to 5; The modified carbon nanofiber is a carbon nanofiber with a rare earth hydroxide coated on the surface; The preparation method does not use surfactants or dispersants.

2. The preparation method according to claim 1, characterized in that: The rare earth hydroxide exists on the surface of the carbon nanofiber in the form of whiskers.

3. The preparation method according to claim 1, characterized in that: The dispersion medium of the carbon nanofiber dispersion is a mixture of water and C1-C6 fatty alcohol, and the solvent of the rare earth soluble salt solution is a mixture of water and C1-C6 fatty alcohol.

4. The preparation method according to claim 1, characterized in that: The concentration of the rare earth soluble salt solution is 0.03-0.06 mol / L.

5. The preparation method according to claim 1, characterized in that: The alkaline compound containing two or more amino groups is selected from one or more of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The closed container is a hydrothermal reactor with a polytetrafluoroethylene liner.

7. Use of the modified carbon nanofibers obtained according to the preparation method according to any one of claims 1 to 6 in improving the strength and / or toughness of polylactic acid.

8. A polylactic acid composition, characterized in that The invention comprises 15 to 35 parts by weight of polylactic acid and 0.01 to 0.5 parts by weight of modified carbon nanofibers obtained by the preparation method according to any one of claims 1 to 5.

9. The polylactic acid composition according to claim 8, characterized in that The invention also comprises 2 to 9 parts by weight of aromatic polyester, 0.05 to 1.5 parts by weight of antioxidant, 0.3 to 2 parts by weight of plasticizer, and 0.05 to 1.5 parts by weight of vegetable oil.

Citation Information

Patent Citations

  • Preparation method of rare earth toughening carbon / carbon composite material

    CN102351556A

  • Lanthanum hydroxide nanowhiskers and preparation method and application thereof

    CN111235624A

  • Preparation method of carbon fiber / rare earth oxide nanowire mixed reinforcement, as well as obtained material and application of carbon fiber / rare earth oxide nanowire mixed reinforcement

    CN113846482A